Recipes for Change validation report: Papas a la Huancaina in Bolivia - Norman, James (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
The main climate risks to potato agriculture in the main cultivation regions of Bolivia are: (i) increased temperatures, and potential effects on growth and transpiration rates; (ii) enhanced climatic variability and prevalence of extreme events, primarily in the intensity and frequency of precipitation levels and temperature; (iii) consequent effects on the growing season. The key adaptation measures for managing the foreseen impacts of climate change within the region are: (i) improved water management and cultivation practices; (ii) improved cultivars, including the adoption of temperature and drought resilient varieties; and (iii) promoting access to, and ensuring continued support of, assets (human, social, financial, political) necessary for coping with both climatic and non-climatic stressors. CCAFS validates the climate threats and solutions highlighted in the IFAD statements below. CCAFS also identifies the fact that the livelihoods of farmers engaged in potato production in Bolivia are subject to multiple stressors, many of which are linked with (but not primarily driven by) changes in the climate. Alleviation of the risks posed by climate change therefore also entails alleviating risks posed by non-climatic stressors. CCAFS also notes that IFAD lists the introduction of 'hardy varieties' as one of their ASAP solutions. However, it is not clear if this means 'improved' varieties developed through a formal breeding programme, or the transfer of local landraces and varieties between locations in order to exploit existing traits. Both may be valid adaptation responses. CCAFS would also add the importance of ex situ and in situ conservation of genetic diversity, for example in Peru at the CIP genebank and at the Parque de la Papa, as critical resources for current and future adaptation. IFAD-identified climate threats to potatoes:  Increased temperatures  Changes in growing seasons  Increased incidence of extreme weather events ASAP solutions:  Introduction of more appropriate and hardy varieties of potatoes  More sustainable practices with yields maintained or even increased